PERAN GURU DALAM MENINGKATKAN KUALITAS BACA AL-QUR`AN SANTRI PUTRI KELAS AWALIYAH “A” - Nur Qomari (Jurnal Studi Pesantren, 2023)
The purpose of this research is to determine the role of teachers in improving the quality of Qur'an recitation at Majlis Tarbiyatul Qur'an PP. Miftahul Ulum Atthohirin Gondanglegi Kulon, Gondanglegi sub-district, Malang regency. Additionally, the study aims to investigate the impact of the teachers' role on the students (santri) of PP Miftahul Ulum Atthohirin. This research adopts a field research approach and uses a descriptive qualitative method. Data collection is conducted through interviews, participant observation, and documentation. Data validity is ensured through triangulation of data sources, which involves using various sources to obtain information, and triangulation of methods by comparing data from interviews, observations, and documentation. The data is analyzed through several steps, including data reduction, data display, and verification, leading to drawing conclusions. The research findings indicate that the role of teachers in improving the quality of Quranic recitation is crucial in nurturing students to become better readers of the Qur'an. Teachers play a pivotal role in the Quranic education process, as they are responsible for producing students who are skilled in reading the Qur'an. Keywords: Theacher’s Role, Reading Proficiency, Al-Qur’an